Radiation Field Inside a Reactor Made of Glass Fiber Meshes Coated with TiO2 - Esterkin, Carlos (2002)
A photocatalytic reactor for treating polluted gaseous streams was developed with a flat-plate configuration and parallel, glass-fiber meshes coated with TiO2. It was irradiated from both sides with UV light provided by tubular lamps placed at both sides of the reactor. The first step in the description of the reactor performance is the knowledge of the local values of radiation intensities. The radiation field was modeled by special adaptation of the ray-tracing technique. The model uses two optical properties of the glass-fiber meshes: transmittance and reflectance. To validate the mathematical description of the reactor with experiments, the exiting radiative flux from one side was measured using a precise UV detector. Predictions show a maximun error of 8.3% with respect to experimental values measured at the center of the apparatus. This description of the radiation distribution is indispensable to model the photooxidation reaction.